Canales de distribución y competitividad en la asociación de mujeres emprendedoras Cuilche Salas. - Caiza Toaquiza, Erika Johana (2020)
The associations are based on solidarity, cooperation and reciprocity relationships, privileging work and the human being as an individual who finishes his activity, which is addressed to the good living and harmony with nature more than the appropriation, profit and accumulation of capital. The Association which is located in ‘San Juan de Pastocalle’ Parish, Latacunga Canton has these problems. Its main market is ‘Mogollón’ market in the city of Latacunga. The association requires rent freight in order to get to the market. It varies between 8 to 10 dollars. These prices are similar to the competition; it avoids an unfair competition and an improper handling of the distribution channels. The purpose of the research study determined the relationship between the distribution channels and the competitiveness of the Association of Women Entrepreneurs of Cuilche Salas, in ‘San Juan de Pastocalle’ Parish, Cotopaxi Province, who intend to offer a more competitive product to strengthen the organizational, social and economic capacity. A reliable literature review was used to guarantee the veracity of the information. In addition, the descriptive methodology and techniques such as: interviews, observation sheet were used to determine the real situation. Then, an internal analysis related to the distribution channel was used to know how the Association is working now. A competitive analysis related to the use of other types of distribution channels by applying the competitive profile matrix which determined the best distribution channel. The next step was to make a relationship with the association channel for financial improvement related to another distribution channel. In conclusion, the components of competitiveness generated an effective proposal for distribution channels direct cash flow analysis and it was recommended that the association should implement a long indirect distribution channel where production increases and costs decrease in spite of the sale price is lower, but when selling in high volumes, the association receives more surplus.